Complex collaboration building the capabilities for working across boundaries - Beyerlein, Michael Martin; Johnson, D. A.; Beyerlein, Susan T. (Emerald, 2004)
Complex collaboration refers to situations where working together effectively across boundaries is critical for complex projects and problems. Complex collaboration refers to knowledge-intensive business processes that require highly interactive communication, coordination, negotiation, research and/or development. This work often involves projects of large scope and long duration. Such projects may cross disciplinary, organizational, national, and/or cultural boundaries. The challenges of managing such situations include ambitious schedules, conflict of cultures and practices, massive amounts of information, multiple languages, and ambiguity of roles and responsibilities. Complex collaboration represents a capability that is essential to effective execution in such situations as new product development, mergers and acquisitions, joint ventures, and supply chain management, as well as large government projects. A number of issues emerge in examining complex collaboration, including: unit of analysis, critical relationships, resource development, virtual teaming, key skills, and improvement processes. The chapters in this volume address these issues and share examples, including: the Joint Strike Fighter program at Lockheed-Martin, Solectrons integrated supply chain, and IMDs partnership with MIT. Models of collaborative capability and capacity provide the facets of a framework for understanding these complex alliances and partnerships.
Keywords: Personnel management.; elektronické knihy; electronic books